Susceptibility of N'Dama and Boran cattle to tsetse-transmitted primary and rechallenge infections with a homologous serodeme of Trypanosoma congolense - Paling, R.; Moloo, S.K.; Scott, J.T.; McOdimba, F.A.; Logan-Henfrey, L.L.; Murray, M.; Williams, D.J.L. (Wiley, 1991)
Summary Eight trypanotolerant N'Dama cattle controlled an infection of Trypanosoma congolense IL Nat 3.1 transmitted by Glossina marsitans centralis, more efficiently than a group of similarly infected trypanosuscepliblc Boran cattle. All eight N'Damas maintained their PCV above 15% throughout the primary infection whereas the PCV of six of the eight Borans dropped below 15%; these latter animals were treated with diminazene aceturate to prevent possible death. Lymphocyte, neutrophil and platelet counts also decreased in the Boran during the primary infection. In contrast, a lymphocytosis was observed in the N'Dama; and although the neutrophil and platelet counts decreased, the drop was less severe than in the Boran. Two years after the primary infection and immediately prior to a homologous rechallenge infection, all eight N'Damas had neutralizing anti‐metacyclic trypanosome variant‐specific antibodies present in their sera compared to five of the eight Borans. Following the homologous rechallenge infection the eight N'Damas became parasitacmic but there were no alterations in their erythrocyte or leukocyte counts. The Borans became highly parasitacmic and developed severe, chronic anaemia and leukopacnia. Thus, the trypanotoleranl N'Damas controlled a primary infection of T. congolense more efficiently than trypanosusceptible Boran cattle and eliminated a homologous rechallenge infection without the pathology associated with the disease.